2018 International Conference on Biometrics (ICB) 2018
DOI: 10.1109/icb2018.2018.00042
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Study of Child Face Recognition

Abstract: We present a longitudinal study of face recognition performance on Children Longitudinal Face (CLF) dataset containing 3, 682 face images of 919 subjects, in the age group [2,18] years. Each subject has at least four face images acquired over a time span of up to six years. Face comparison scores are obtained from (i) a state-of-the-art COTS matcher (COTS-A), (ii) an open-source matcher (FaceNet), and (iii) a simple sum fusion of scores obtained from COTS-A and FaceNet matchers. To improve the performance of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 25 publications
1
35
0
Order By: Relevance
“…In recent years, several works have been published that demonstrated the influence of demographics on commercial and open-sources face recognition algorithms. Studies [56], [46], [16], [66] analysing the impact of age demonstrated a lower biometric performance on faces of children. Studies [76], [3], [2], [61] analysing the effect of gender on face recognition showed that the recognition performance of females is weaker than the performance on male faces.…”
Section: A Estimating Bias In Face Recognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, several works have been published that demonstrated the influence of demographics on commercial and open-sources face recognition algorithms. Studies [56], [46], [16], [66] analysing the impact of age demonstrated a lower biometric performance on faces of children. Studies [76], [3], [2], [61] analysing the effect of gender on face recognition showed that the recognition performance of females is weaker than the performance on male faces.…”
Section: A Estimating Bias In Face Recognitionmentioning
confidence: 99%
“…Identities Images Attributes (number classes) Ricanek et al [56] 0.7k 8.0k Age (2) Deb et al [16] 0.9k 3.7k Age (cont.) Srinivas et al [66] 1.7k 9.2k Age (2) Michalski et al [46] -4.7M Age (cont.)…”
Section: Workmentioning
confidence: 99%
“…For there should be a number of images/samples each participating child/subject during a specified of age. To analyze the capability of face recognition technology to trace lost children, several databases have been created [6], [104], [105].…”
Section: B Missing Children Identificationmentioning
confidence: 99%
“…Children Longitudinal Face (CLF) dataset [105] consists of 3,682 face images of 919 participating children aged between two and 18 years. Each child had at least four face images acquired over a time span of up to six years.…”
Section: B Missing Children Identificationmentioning
confidence: 99%
“…Several studies have analyzed the extent to which facial aging affects the performance of AFR. Two major conclusions can be drawn based on these studies: (i) Performance decreases with an increase in time lapse between subsequent image acquisitions [25,14,22], and (ii) performance degrades more rapidly in the case of younger individuals than older individuals [22,15]. Figure 1 illustrates that a state-of-the-art face matcher (CosFace) fails when it comes to matching an enrolled child in the gallery with the corresponding probe over large time lapses.…”
Section: Introductionmentioning
confidence: 98%